2016
DOI: 10.1007/s10620-016-4222-2
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Analysis and Critical Appraisal of the Quality of the Scientific Evidence and Conflicts of Interest in Practice Guidelines (2005–2013) for Barrett’s Esophagus

Abstract: Majority of the BE guideline fail to meet the AGREE II domains, and most of the recommendations are level B or C quality evidence. Further interventions are necessary to improve the overall quality of the guidelines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 41 publications
(61 reference statements)
0
10
0
Order By: Relevance
“…Nineteen studies relied on author declarations of FCOI, either through surveys sent to the authors 36,41 or through the declaration section of included guidelines or the sponsoring society of the guideline. [10][11][12][13][14][15][16]24,29,31,32,34,[37][38][39][40]43 Eleven studies evaluated conflict of interest using the CMS-OP or other national databases. 8,9,17,18,[25][26][27]30,33,44,45 Seven studies evaluated conflicts of interest through external searches.…”
Section: Identification Of Conflicts Of Interestmentioning
confidence: 99%
“…Nineteen studies relied on author declarations of FCOI, either through surveys sent to the authors 36,41 or through the declaration section of included guidelines or the sponsoring society of the guideline. [10][11][12][13][14][15][16]24,29,31,32,34,[37][38][39][40]43 Eleven studies evaluated conflict of interest using the CMS-OP or other national databases. 8,9,17,18,[25][26][27]30,33,44,45 Seven studies evaluated conflicts of interest through external searches.…”
Section: Identification Of Conflicts Of Interestmentioning
confidence: 99%
“…This lack of transparency makes it difficult for readers and users of the guidelines to assess undue influence and bias and, according to several studies, numerous conflicts of interest are evident when information is disseminated. [23][24][25][26][27] However, it is necessary to highlight the effort made by some groups or entities developing CPGs to reduce the possibility of developers having conflicts of interest. This is an effort in which transparency (understood as a way of operating so that the public can see clearly what actions are carried out) and accessibility have been cited as the most important aspects to assess conflict of interest policies in health organizations.…”
Section: Discussionmentioning
confidence: 99%
“…According to the search criteria, there were 9 CPG reviews (Table 2), of which 7 concluded that there is low disclosure rates of conflicts of interest. [23][24][25][26][27][28][29] However, Feuerstein, in different studies and with the support of several researchers, highlights that this type of publication has multiple conflicts of interest. [23][24][25][26][27] The other 2 reviews do not address this issue.…”
Section: Clinical Practice Guidelinesmentioning
confidence: 99%
“…The main problem of all guidelines is the level of evidence of the statements and recommendations proposed. In a systematic analysis using the AGREE II format for practice guidelines evaluation it was found that most of the recommendations for BE guideline were of level B or C for quality evidence and that they failed to meet the AGREE II domains (36). Although the new guidelines are more convergent that the previous ones, there are still many studies to be carried out evaluating the correct management of BE concerning the best technique to be used and avoiding the over or the under-treatment of the patients.…”
Section: Hgd-endoscopic Interventionsmentioning
confidence: 99%